1988
DOI: 10.1001/archotol.1988.01860240063025
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Major Events of Pharyngeal Swallowing

Abstract: swallowing depends on the synergistic motion of the tongue, larynx, and pharyngeal wall to develop a bolus pressure gradient for bolus transit. However, few studies have provided timing relationships for clinical evaluations. To examine the timing relationships of pharyngeal anatomic motion, pressure generation, and bolus transit in the normal swallow, this study uses a new method, manofluorography, to correlate these swallowing aspects. Thirty-one events were timed by analyzing five swallows each in 14 normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
3

Year Published

1990
1990
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 11 publications
2
48
0
3
Order By: Relevance
“…Therefore, it might be hypothesized that retention develops when these driving forces become deficient. On the other hand, the propagated pharyngeal contraction may facilitate pharyngeal clearance as it seems to follow the bolus tail [5,6]. In addition, a pharyngeal shortening most pronounced between the arytenoids and the valleculae has been observed during deglutition [6,7].…”
mentioning
confidence: 99%
“…Therefore, it might be hypothesized that retention develops when these driving forces become deficient. On the other hand, the propagated pharyngeal contraction may facilitate pharyngeal clearance as it seems to follow the bolus tail [5,6]. In addition, a pharyngeal shortening most pronounced between the arytenoids and the valleculae has been observed during deglutition [6,7].…”
mentioning
confidence: 99%
“…Recent studies have reported normal values for pharyngeal transit times [2,3]. Qualitative VDF and quantitative esophageal data have previously been reported for subjects with myopathy [4][5][6][7].…”
Section: Abstract Measurement Of Kinematic Pharyngeal Transitmentioning
confidence: 99%
“…Patients have been shown to refuse a food consistency if it takes 10 s or more for oral and pharyngeal transit of a bolus. Normally the oral and pharyngeal phases of swallowing each take only 1 s or less [12]. Oral intake was discontinued for Mr. T during Swallowing therapy because he aspirated more than 10% of the liquid bolus during the modified barium swallow study.…”
Section: Commentsmentioning
confidence: 99%